Bempegaldesleukin (BEMPEG; NKTR‐214) efficacy as a single agent and in combination with checkpoint‐inhibitor therapy in mouse models of osteosarcoma. Issue 8 (25th November 2020) - Hennessy, Marlene; Wahba, Andrew; Felix, Kumar; Cabrera, Mariella; Segura, Maria Gabriela; Kundra, Vikas; Ravoori, Murali K.; Stewart, John; Kleinerman, Eugenie S.; Jensen, Vanessa Behrana; Gopalakrishnan, Vidya; Pena, Rhoneil; et al.
Abstract: Survival of patients with relapsed/refractory osteosarcoma has not improved in the last 30 years. Several immunotherapeutic approaches have shown benefit in murine osteosarcoma models, including the anti‐programmed death‐1 (anti‐PD‐1) and anti‐cytotoxic T‐lymphocyte antigen‐4 (anti‐CTLA‐4) immune checkpoint inhibitors. Treatment with the T‐cell growth factor interleukin‐2 (IL‐2) has shown some clinical benefit but has limitations due to poor tolerability. Therefore, we evaluated the efficacy of bempegaldesleukin (BEMPEG; NKTR‐214), a first‐in‐class CD122‐preferential IL‐2 pathway agonist, alone and in combination with anti‐PD‐1 or anti‐CTLA‐4 immune checkpoint inhibitors in metastatic and orthotopic murine models of osteosarcoma. Treatment with BEMPEG delayed tumor growth and increased overall survival of mice with K7M2‐WT osteosarcoma pulmonary metastases. BEMPEG also inhibited primary tumor growth and metastatic relapse in lungs and bone in the K7M3 orthotopic osteosarcoma mouse model. In addition, it enhanced therapeutic activity of anti‐CTLA‐4 and anti‐PD‐1 checkpoint blockade in the DLM8 subcutaneous murine osteosarcoma model. Finally, BEMPEG strongly increased accumulation of intratumoral effector T cells and natural killer cells, but not T‐regulatory cells, resulting in improved effector:inhibitory cell ratios. Collectively, these data in multiple murine models of osteosarcoma provide a path toward clinical evaluation of BEMPEG‐based regimens in human osteosarcoma. Abstract : What's new? Despite treatment, many patients with osteosarcoma are at high risk for metastatic disease. Such cases of advanced osteosarcoma present significant therapeutic challenges, owing largely to a lack of novel and optimized treatment strategies. Here, the authors investigated the efficacy of bempegaldesleukin (BEMPEG; NKTR‐214), a novel CD122‐preferential interleukin‐2 pathway agonist, in murine models of osteosarcoma. Experiments show that BEMPEG monotherapy decreases metastatic relapse in lung and bone tissue and prolongs survival in mice. Durable tumor growth was achieved with combined BEMPEG and anti‐CTLA‐4 or anti‐PD‐1 checkpoint inhibition. The data provide a scientific rationale for clinical evaluation of BEMPEG for osteosarcoma treatment.